Digitalisasi Pemasaran Produk Unggulan Daerah: Strategi BUMDesa Langgam Sako Menuju Sustainable Competitive Advantage - Alwie, Alvi Furwanti; Azlina, Nur; Taufik, Taufeni; Iznillah, M. Luthfi; Maulana, Gilang Eka; Ramadhan, Gian Riovi (Unri Conference Series: Community Engagement, 2024)
Village-Owned Enterprises or BUMDesa Langgam Sako, Bengkalis Regency, has great potential in regional superior products, but faces challenges in marketing products effectively. This article discusses the community service activities carried out by the community service team in order to support BUMDesa Langgam Sako to achieve Sustainable Competitive Advantage through marketing digitalization. The method of implementing activities begins with an analysis of the needs and potential of BUMDesa Langgam Sako. Furthermore, the procurement of a marketing website was carried out to provide a digital platform that facilitates the promotion and sale of regional superior products. The website was designed with user-friendly features and optimized for internet searches. Online marketing training was provided to BUMDesa members through intensive workshops covering the use of social media, digital content creation, and online marketing strategies as an effort to strengthen BUMDesa's ability to manage their business more effectively and achieve Sustainable Competitive Advantage. The results of this activity showed a significant increase in the visibility of regional superior products online. BUMDesa members also demonstrated improved skills in managing digital marketing and business in general. This activity successfully assisted BUMDesa Langgam Sako in achieving a sustainable competitive advantage and positively impacted the local economy through the increased contribution of flagship product sales, namely Bengkalis woven batik, it has also become a source of income for artisans and strengthened the village's economic competitiveness at the regional level. This initiative underscores the importance of digitalization for the overall economic development of the village.